Strategy for Improving Restaurant Taxpayer Compliance Assistance through a Peddling Approach for Business Actors at the Surabaya City Regional Revenue Agency - Yuniaparas; M. Taufiq; Fitria Utami, Anisa (Pascasarjana Universitas Mataram, 2025)
This article discusses a strategic approach to improving taxpayer compliance among restaurant owners in Surabaya through a method known as “shadowing.” The peddling approach involves direct supervision and education, where tax officials engage with business operators to increase their understanding of tax obligations and improve their accounting systems. The results show a significant increase in transparency and accountability in tax reporting, leading to a reduction in tax evasion. Despite the successes, challenges remain, particularly regarding resistance from some business owners and a lack of understanding of tax responsibilities. Continued efforts from the government are essential to provide better education and create an enabling environment for tax compliance. This study concludes that a collaborative ecosystem between government and businesses can foster a fair, transparent, and sustainable tax environment, ultimately contributing to regional development and community welfare.